Enlarged cross-sectional area of the left vagus nerve in patients with major depressive disorder - Schreiber, Lisa Sofie; Wozniak, David; Scheller, Erik; Böttcher, Elise; Pelz, Johann Otto; Schmidt, Frank M. (Frontiers in Psychiatry, 2023)
Purpose: Autonomic dysfunction and a chronic low-grade inflammation are supposed to play a role in the etiology of major depressive disorder (MDD). The vagus nerves (VN) form a major part of the parasympathetic nervous system and of the gut-brain axis. They are supposed to exert anti-inflammatory and epithelial barrier protective effects in the gut. A reduced vagal activity was described in patients with MDD. We aimed to examine the VN in patients with MDD with high-resolution ultrasound (HRUS) and hypothesized that the cross-sectional area (CSA) and the echogenicity of the VNs were altered in comparison to healthy controls. Materials and Methods: The echogenicity (gray scale mean) and the CSA of the cervical VNs at the level of the thyroid gland and both median nerves were examined with HRUS in 50 patients with MDD and 50 matched healthy controls. Results: The left VN-CSA was significantly larger in the MDD group compared to the control group (1.7 ± 0.4 mm2 versus 1.5 ± 0.4 mm2; p = 0.045). The CSA of the right VN and both median nerves (MN) were similar between groups. In MDD subgroup analyses, recurrent depressive disorders were the main contributing factor for the left VN-CSA enlargement. Echogenicity was not altered in the VN and MN between groups. Conclusion: The enlargement of the left VN-CSA in patients with MDD, and especially in these patients with recurrent depressive disorders, might turn out as a promising imaging biomarker. Longitudinal studies are warranted to examine whether the VNs-CSA change in the course of MDD.